Pyramiding of rust resistance genes in wheat utilizing male sterility mediated marker-assisted recurrent selection - Springfield, Lezaan Sevone (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.